Sediment handling at run-of-river projects in Himalayan rivers using sediment rating curves - Pandit, Hari Prasad (Nepalese Journal of Engineering, 2005)
Most of the Himalayan rivers are characterized by young and fragile geology with steep catchment. The incessant and stochastic character of rainfall in the mountain catchment generates enormous amount of sediment in these rivers. Not only the higher sediment concentration but also the domination of hard minerals such as quartz have caused severe damage to the water projects. Therefore, the conventional methods of sediment handling found to be satisfactory in other region of the world have been found to be inadequate in this region. This paper puts forth sediment problems and sediment related wear and tear in RoR hydropower projects constructed in Himalayan Rivers. Discharge and sediment data of Jhimruk river at Jhimruk Hydropower Project have been presented and analyzed to derive sediment duration and rating curves for the months of June, July, August and September. Amongst four months of sediment data analyzed, July is found to be the extreme one when 4,000 ppm or more exists for about 30 % of the time. The relations between sediment load and discharge have been established by regression analyses. The statistical analysis carried out revealed that the relations derived between sediment load and discharge are statistically significant. As real time sediment monitoring is a quite expensive task, these relations may give very useful information to the projects in Jhimruk River basin, which do not have setup for real time monitoring of sediment concentration. Keywords: Himalayan rivers, sediment duration curve, sediment rating curve. Nepalese Journal of Engineering Vol.1(1) 2005 pp.39-45